All Days 2012
DOI: 10.2118/147409-ms
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Enhancement of Elastomers for Improved Downhole Barrier Performance

Abstract: The oil and gas industry is continuously looking for material and tool designs with more robustness that provides greater operational flexibility in aggressive environments. New elastomeric systems that have been enhanced at the nanometer scale have been engineered to address these needs. Nano-enhanced EPDM showed 95-percent lower swelling rate in oil at ambient temperature. Nano-enhanced HNBR compound exhibited 15 times lower absorption in 300°F hydrocarbon fluid. Nano-enhanced FEPM compound sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Another example of NBR performance in sour condition was reported in SPE (Society of Petroleum Engineers) as nano-enhancement of elastomer for improved downhole barrier performance. 6 In this study, nano-enhanced NBR (nanoscale coated by polymer system containing branched polyethyleneimine) and polyacrylic acid, with the final crosslinking by glutaraldehyde showed a 50% reduction in the degradation effect of H 2 S in physical properties. It was observed that uncoated NBR could deteriorate in the physical properties like tensile strength in the sour condition of 5% CO 2 /10% H 2 S/85% CH 4 in aging temperature 148.9 C and aging pressure 1.38 MPa under CL-5 oil immersion for 24 h. The tensile strength and the elongation at break of aged NBR reduced by approximately 75% and 25%, respectively.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Another example of NBR performance in sour condition was reported in SPE (Society of Petroleum Engineers) as nano-enhancement of elastomer for improved downhole barrier performance. 6 In this study, nano-enhanced NBR (nanoscale coated by polymer system containing branched polyethyleneimine) and polyacrylic acid, with the final crosslinking by glutaraldehyde showed a 50% reduction in the degradation effect of H 2 S in physical properties. It was observed that uncoated NBR could deteriorate in the physical properties like tensile strength in the sour condition of 5% CO 2 /10% H 2 S/85% CH 4 in aging temperature 148.9 C and aging pressure 1.38 MPa under CL-5 oil immersion for 24 h. The tensile strength and the elongation at break of aged NBR reduced by approximately 75% and 25%, respectively.…”
Section: Introductionmentioning
confidence: 64%
“…Generally, a blister is related to rapid gas decompression (RGD) for oilfield elastomers and typical elastomer compounds used for packer can have RGD damage if the pressure drop or decompression rate is high enough. 6,[14][15][16][17] In our aged test condition, the depressurize rate was very slow (6.9 kPa/min); hence the blister might be related to the formulation of the elastomer such as plasticizer and other additives or interaction with 70% hydrocarbon fluid (70% heptane/20% cyclohexane/10% toluene) in multiphase (gas/seawater/hydrocarbon phase).…”
Section: Visual Inspectionmentioning
confidence: 99%